(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2026)
This paper examines equity and inclusion in development initiatives affecting Small Ethnic Communities (SECs)[1] in Chittagong Hill Tracts (CHTs), Bangladesh, through a rural development project supported by Asian Development Bank (ADB) as a case study. Using a multi-method approach, the study analyzed relevant policies and legal instruments, geopolitical conditions, project records and primary data were collected through field observations and key informant interviews. Results show that sustained engagement with SECs through participatory consultations, village mapping, and context-specific interventions were essential to achieve development goals with customary practices within a dual legal system. This was accomplished by following the national legal frameworks in Bangladesh, in collaboration with the safeguard policies of development partner. Interventions, such as improvement of road network, market sheds, gravity flow distribution of water, promotion of local medicinal plant cultivation along with drawing on indigenous knowledge in creating alternative income opportunities enhanced the income and quality of life as well as facilitated in sustaining their cultural practices. These experiences demonstrate how alignment of safeguard principles, local practices, and participatory approaches can foster more inclusive outcomes, contributing to global development agendas in Bangladesh such as SDG 10 on reducing inequalities and SDG 17 on partnerships for the goals. J. Asiat. Soc. Bangladesh, Sci. 51(2): 207-222, December 2025